CORRELATION OF SLEEP QUALITY ON NUTRITIONAL STATUS AND THE INCIDENT OF ANEMIA IN STUDENTS AT MTS AL-MUKHSIN - Tiara Anggita; Khoirul Anwar (Journal of Global Nutrition, 2023)
Anemia is a condition where the hemoglobin value is <12 g/dL and often occurs in adolescent girls due to many factors such as lack of nutritional intake which can also affect the nutritional status of adolescents. The purpose of this study was to analyze the relationship between sleep quality, protein intake, vitamin C and iron to nutritional status and the incidence of anemia in female students at MTs Al-Mukhsin. The study was conducted at MTs Al-Mukhsin in July 2023 with a sample size of 55 subjects from classes VIII and IX using simple random sampling technique through a cross sectional approach and analyzed using the Spearman rank correlation test. Based on descriptive analysis 54,5% had good nutritional status, 67,3% of subjects had poor sleep quality, 45,5% had anemiat. The results of Spearman rank correlation analysis between sleep quality and nutritional status showed no relationship (p = 0,143). The results of the analysis of sleep quality with the incidence of anemia showed no relationship (p = 0,215). The conclusion of this study is that there is no significant relationship between sleep quality and nutritional status and the incidence of anemia in female students at MTs Al-Mukhsin.